STRATEGI DAN TEKNIK PENERJEMAHAN LISAN (Universitas Negeri Jakarta, 2015)
Translation is generally defined as activities divert the messages conveyed in the source language to the target language. Proposed definitions vary according to the background and perspective, so that this definition can be weak, strong or browse each other. In practice, in terms of process and product of translation, we know there are two types of translation, namely the translation of written and oral translation. In this paper, we discuss some strategies and techniques oral translation or interpretation as well as some common aspects with written translation, especially in the Japanese language. The aim of this article is to clarify the strategy and technic of interpretation, also understood as oral translation. There are many technic and strategy of interpretation proposed by scholars. Some of the technics are similar, but some are overlapping and show inconsistency. First, existing strategies and technics of interpretation are reviewed in terminological and conceptual are pointed out. Then, based on analysis, the new technics classifications are proposed.